Water-absorbent resin composition, water stop material, and cable

By combining a chelating agent with a specific range of iron (III) chelating stability constant with water-absorbent resin particles, a water-absorbent resin composition is formed, and the problem of water-absorbent resin being easily degraded and difficult to decompose at high temperatures in the prior art is solved, and a combination of high water-stopping properties and excellent decomposition properties is achieved.

CN119836454APending Publication Date: 2025-04-15SUMITOMO SEIKA CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380066820.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-22
Filing Date
2023-09-22
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The water-absorbent resin used in the existing water stop materials is prone to deterioration under high temperature environments, and its stability is difficult to decompose in nature, resulting in an increase in environmental load.

Method used

By combining the chelating agent with an iron (III) chelating stability constant of 19.0 or above and 24.0 or below with the water-absorbent resin particles, a water-absorbent resin composition is formed, thereby improving its stability at high temperature and decomposition properties in nature.

Benefits of technology

The water-absorbent resin composition has excellent decomposition properties while high water-stopping properties, and is suitable for use in water-stopping materials, reducing environmental load.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

Provided are: a water-absorbent resin composition which has excellent decomposition performance while having high water-stop performance, and which can be suitably used as a water-stop material; and a water-stop material which contains the water-absorbent resin composition. This water-absorbent resin composition contains water-absorbent resin particles and a chelating agent, and the chelating agent has an iron (III) chelating stability constant (logKML) of from 19.0 to 24.0 (inclusive) and a 30-second swelling height of 6.0 mm or more. The water-absorbent resin composition of the present invention has excellent decomposition performance while having high waterstop performance, and can be suitably used as a waterstop material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a water-absorbent resin composition, a water-stopping material and a cable. Background Art

[0002] It is known that water-absorbent resins have excellent water absorption capacity and can exhibit water-stopping effects, and therefore can be used in various applications requiring water-stopping properties. For example, water-absorbent resins are used as water-stopping materials for communication cables such as optical cables and power cables.

[0003] Patent Document 1 discloses a technique in which a water-stopping material formed by enclosing a water-absorbent sheet containing a water-absorbent resin in an exterior material is used to prevent the gel of the water-absorbent resin that swells after absorbing water from seeping out.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2014-147281 Summary of the invention

[0007] Problems to be solved by the invention

[0008] For the water-absorbing resin used in the above-mentioned water-stopping material (e.g., water-stopping strip), it is important not only to have swelling properties that can immediately stop water intrusion, but also to have the property that the gel (the swollen water-absorbing resin) is not easily degraded by the heat generated by the cable. In other words, the water-absorbing resin used in the water-stopping material is required to have both swelling properties and stability.

[0009] On the other hand, if the waterproof material is soaked in water, the water-absorbing resin may flow out from the soaked part to the nature. Therefore, if the stability of the water-absorbing resin is high, it will be difficult to decompose in the nature. That is, for the waterproof material, it is important to have a water-absorbing resin that can maintain a balanced waterproof performance and decomposition performance. From this point of view, a water-absorbing resin that can achieve both high waterproof performance and reduced environmental load is strongly required.

[0010] The present invention has been made in view of the above problems, and an object of the present invention is to provide a water-absorbing resin composition which has high water-stopping performance and excellent decomposition performance and can be suitably used in a water-stopping material, and a water-stopping material containing the composition.

[0011] Methods used to solve problems

[0012] The present inventors have conducted intensive studies to achieve the above object and have found that the above object can be achieved by using a chelating agent having a specific chelation stability constant (logKML) for iron (III), thereby completing the present invention.

[0013] That is, the present invention includes, for example, the subject matters described in the following items.

[0014] Item 1

[0015] A water-absorbent resin composition comprising water-absorbent resin particles and a chelating agent, wherein the chelating agent has an iron (III) chelate stability constant (logKML) of 19.0 or more and 24.0 or less and a 30-second swelling height of 6.0 mm or more.

[0016] Item 2

[0017] The water-absorbent resin composition according to item 1, comprising 0.001 to 3.00 parts by mass of the chelating agent based on 100 parts by mass of the water-absorbent resin particles.

[0018] Item 3

[0019] The water-absorbent resin composition according to item 1 or 2, wherein the water-absorbent resin particles have a structure obtained by cross-linking a polymer of a water-soluble ethylenically unsaturated monomer.

[0020] Item 4

[0021] A water-stopping material comprising the water-absorbent resin composition according to any one of items 1 to 3.

[0022] Item 5

[0023] A cable comprising the water-stopping material described in item 4.

[0024] Effects of the Invention

[0025] The water-absorbent resin composition of the present invention has high water-stopping performance and is also excellent in decomposition performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram of a measuring device used to measure the swelling height of a water-absorbent resin composition.

[0027] Figure 2 This is a schematic diagram of a measuring device used to evaluate the water stopping rate of a water-absorbent resin composition. DETAILED DESCRIPTION

[0028] The embodiments of the present invention are described in detail below. It should be noted that in this specification, the expressions "comprising" and "including" include concepts such as "comprising", "including", "consisting essentially of", and "consisting only of".

[0029] For the numerical range recorded in stages in this specification, the upper limit or lower limit of the numerical range in a certain stage can be arbitrarily combined with the upper limit or lower limit of the numerical range in other stages. For the numerical range recorded in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment or the value unambiguously derived from the embodiment. In addition, in this specification, the numerical value connected with "~" refers to the numerical range including the numerical values ​​before and after "~" as the lower limit and upper limit.

[0030] 1. Water-absorbent resin composition

[0031] The water-absorbent resin composition of the present invention contains water-absorbent resin particles and a chelating agent having an iron (III) chelate stability constant (logKML) of 19.0 or more and 24.0 or less. The water-absorbent resin composition of the present invention has a 30-second swelling height of 6.0 mm or more.

[0032] The water-absorbent resin composition of the present invention has high water-stopping performance and excellent decomposition performance. That is, the water-absorbent resin composition of the present invention has swelling performance that can immediately prevent water intrusion, and can have the property that the swollen water-absorbent resin is not easily degraded to the extent that the decomposition performance is not impaired. Therefore, the water-absorbent resin composition of the present invention can be suitably used for various water-stopping materials, can impart excellent water-stopping performance to water-stopping materials, and has excellent decomposition performance, so it can also reduce environmental load.

[0033] In the present invention, "the water-absorbing resin composition has excellent water-stopping performance" may mean that the water-absorbing resin composition has the above-mentioned swelling performance and has the property that the swollen water-absorbing resin is not easily deteriorated. In particular, the water-stopping performance of the water-absorbing resin composition can be improved by using the following Figure 2 Evaluation was performed based on the water cutoff rate (%) measured by the device shown.

[0034] (Water-absorbent resin particles)

[0035] The water-absorbent resin particles contained in the water-absorbent resin composition of the present invention are a component for exhibiting water-stopping performance and can be a material that can be a main component of the water-absorbent resin composition. The type of the water-absorbent resin particles is not particularly limited as long as they can provide the composition with a predetermined 30-second swelling height.

[0036] The water-absorbent resin particles contained in the water-absorbent resin composition of the present invention preferably have a structure obtained by crosslinking a polymer of a water-soluble ethylenically unsaturated monomer. In this case, the water-absorbent resin composition can impart excellent water-stopping performance to a water-stop material. The polymer of a water-soluble ethylenically unsaturated monomer may have a structure obtained by crosslinking with an internal crosslinking agent described below, for example, or may have a structure obtained by crosslinking with a post-crosslinking agent described below instead of or in addition to the internal crosslinking agent.

[0037] As water-soluble ethylenically unsaturated monomers, for example, commonly known monomers that can be used for water-absorbent resins can be widely used. As water-soluble ethylenically unsaturated monomers, for example, (meth)acrylic acid (in this specification, "acrylic ..." and "methacrylic ..." are collectively referred to as "(meth)acrylic ...". The same applies hereinafter) and its salts; 2-(meth)acrylamide-2-methylpropanesulfonic acid and its salts; nonionic monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, 2-hydroxyethyl(meth)acrylate, N-hydroxymethyl(meth)acrylamide, and polyethylene glycol mono(meth)acrylate; unsaturated monomers containing amino groups such as N,N-diethylaminoethyl(meth)acrylate, N,N-diethylaminopropyl(meth)acrylate, and diethylaminopropyl(meth)acrylamide, and their quaternary products. These water-soluble ethylenically unsaturated monomers can be used alone or in combination (copolymerization) of two or more. Among them, (meth)acrylic acid and salts thereof, (meth)acrylamide, and N,N-dimethylacrylamide are preferred from the viewpoint of industrial availability, and (meth)acrylic acid and salts thereof are more preferred.

[0038] When acrylic acid and salts thereof are used as these water-soluble ethylenically unsaturated monomers, acrylic acid and salts thereof are used as the main water-soluble ethylenically unsaturated monomers, preferably in an amount of 70 to 100 mol % based on the total molar number of the water-soluble ethylenically unsaturated monomers.

[0039] It should be noted that, in the reverse phase suspension polymerization described later, in order to improve the dispersion efficiency in the hydrocarbon dispersion medium, the water-soluble ethylenically unsaturated monomer can be used as an aqueous solution. The concentration of the monomer in the aqueous solution is usually set to 20% by mass or more and below the saturation concentration, preferably 25 to 90% by mass, more preferably 30 to 85% by mass.

[0040] In the case where the water-soluble ethylenically unsaturated monomer has an acid group such as (meth) acrylic acid, 2-(meth) acrylamide-2-methylpropanesulfonic acid, etc., a water-soluble ethylenically unsaturated monomer in which the acid group is neutralized in advance with an alkaline neutralizer can be used as needed. Examples of such alkaline neutralizers include alkali metal salts such as sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, and ammonia. In particular, in order to simplify the neutralization operation, these alkaline neutralizers can be used in the form of aqueous solutions. The above alkaline neutralizers can be used alone or in combination of two or more.

[0041] Regarding the neutralization degree of the water-soluble ethylenically unsaturated monomer by the alkaline neutralizing agent, in order to improve the water absorption performance by increasing the osmotic pressure of the obtained water-absorbent resin particles and to prevent problems in safety and the like due to the presence of excess alkaline neutralizing agent, it is generally preferred to set the neutralization degree of all acid groups possessed by the water-soluble ethylenically unsaturated monomer to 10 to 100 mol %, more preferably 30 to 80 mol %.

[0042] The water-absorbent resin particles can be produced, for example, by a production method including a step of performing a polymerization reaction using a raw material containing the water-soluble ethylenically unsaturated monomer (hereinafter referred to as a "polymerization step").

[0043] As the polymerization reaction carried out in the polymerization process, for example, reverse suspension polymerization, aqueous solution polymerization, emulsion polymerization, etc. can be cited. From the viewpoint of easily adjusting the 30-second swelling height to a specified range, it is preferred to adopt reverse suspension polymerization in the polymerization process. Reverse suspension polymerization refers to a method in which a poorly soluble monomer is suspended in the above-mentioned dispersion medium in the presence of a dispersion stabilizer, for example, and polymerized. As is well known, reverse suspension polymerization can be a multi-step polymerization in which the monomer is polymerized in multiple steps, for example, it can be a two-step polymerization. In the multi-step polymerization, the initial polymerization reaction is referred to as the first step, and thereafter, the monomers added stepwise after the first step polymerization are referred to as the second step, the third step, etc. in sequence.

[0044] As the dispersion medium used in the reverse suspension polymerization, a hydrocarbon dispersion medium can be used. Examples of hydrocarbon dispersion mediums include: aliphatic hydrocarbons such as n-hexane, n-heptane, n-octane, and light petroleum (ligroin); alicyclic hydrocarbons such as cyclopentane, methylcyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbons such as benzene, toluene, and xylene. Among these dispersion media, n-hexane, n-heptane, and cyclohexane are preferably used because they are easily available in industry, have stable quality, and are inexpensive. These dispersion media can be used alone or in combination of two or more. As the dispersion medium, for example, Exxsol Heptane (manufactured by ExxonMobil: hydrocarbons of heptane and its isomers), Nappar6 (manufactured by ExxonMobil: hydrocarbons of cyclohexane and its isomers), which are known as mixed solvents, can be used.

[0045] The water-soluble ethylenically unsaturated monomer that can be used in the reverse phase suspension polymerization is the same as the above-mentioned water-soluble ethylenically unsaturated monomer, and is preferably (meth)acrylic acid and its salts, (meth)acrylamide, and N,N-dimethylacrylamide from the viewpoint of excellent reactivity, and is more preferably (meth)acrylic acid and its salts. In addition, the water-soluble ethylenically unsaturated monomer may be subjected to a neutralization treatment so that the degree of neutralization is within the above-mentioned range.

[0046] In the polymerization reaction in the polymerization step, especially in the reverse phase suspension polymerization, a thickener may be used as needed. As the thickener, for example, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, carboxymethyl cellulose, polyacrylic acid, polyacrylic acid (partially) neutralized product, polyethylene glycol, polyacrylamide, polyethyleneimine, dextrin, sodium alginate, polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene oxide, etc. can be used.

[0047] As the dispersion stabilizer used in the reversed suspension polymerization, a surfactant can be used, for example, sucrose fatty acid ester, polyglycerol fatty acid ester, sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene glycerol fatty acid ester, sorbitol fatty acid ester, polyoxyethylene sorbitol fatty acid ester, polyoxyethylene alkyl ether, polyoxyethylene alkylphenyl ether, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, alkyl allyl formaldehyde condensation polyoxyethylene ether, polyoxyethylene polyoxypropylene block copolymer, polyoxyethylene polyoxypropyl alkyl ether, polyethylene glycol fatty acid ester, alkyl glucosides, N-alkyl glucamide, polyoxyethylene fatty acid amide, polyoxyethylene alkylamine, phosphate ester of polyoxyethylene alkyl ether, phosphate ester of polyoxyethylene alkyl allyl ether, etc. can be used. Among them, from the dispersion stability aspect of the monomer, sorbitan fatty acid ester, polyglycerol fatty acid ester, sucrose fatty acid ester, etc. are preferred. These surfactants can be used alone or in combination of two or more.

[0048] Regarding the amount of surfactant used, in order to maintain a good dispersion state of the water-soluble ethylenically unsaturated monomer in the hydrocarbon dispersion medium and obtain a dispersion effect consistent with the amount used, it is preferably 0.1 to 30 parts by mass, and more preferably 0.3 to 20 parts by mass, relative to 100 parts by mass of the water-soluble ethylenically unsaturated monomer in the first step.

[0049] In addition, as a dispersion stabilizer, a polymeric dispersant can be used in combination with or in place of a surfactant. As usable polymeric dispersants, maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-modified EPDM (ethylene-propylene-diene terpolymer), maleic anhydride-modified polybutadiene, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, maleic anhydride-butadiene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, ethylene-acrylic acid copolymer, ethyl cellulose, ethyl hydroxyethyl cellulose, etc. can be cited. Among them, maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, etc. are preferred from the perspective of the dispersion stability of the monomer. These polymeric dispersants may be used alone or in combination of two or more.

[0050] The amount of the polymer dispersant used is preferably 0.1 to 30 parts by mass, more preferably 0.3 to 20 parts by mass, relative to 100 parts by mass of the water-soluble ethylenically unsaturated monomer in the first step, in order to maintain a good dispersion state of the water-soluble ethylenically unsaturated monomer in the hydrocarbon dispersion medium and obtain a dispersing effect commensurate with the amount used.

[0051] In the polymerization step, for example, a widely known polymerization initiator can be used. Examples of free radical polymerization initiators include persulfates such as potassium persulfate, ammonium persulfate, and sodium persulfate; peroxides such as methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, di-tert-butyl peroxide, tert-butyl cumyl peroxide, and hydrogen peroxide; and azo compounds such as 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[2-(N-phenylamidino)propane] dihydrochloride, 2,2'-azobis[2-(N-allylamidino)propane] dihydrochloride, and 4,4'-azobis(4-cyanovaleric acid). Free radical polymerization initiators can also be used in combination with reducing agents such as sodium sulfite, sodium bisulfite, ferrous sulfate, and L-ascorbic acid to prepare redox polymerization initiators.

[0052] The lower limit of the amount of the free radical polymerization initiator used in the polymerization step is preferably 0.01 mmol, more preferably 0.05 mmol, relative to 1 mol of the water-soluble ethylenically unsaturated monomer used, from the viewpoint of polymerization stability. In addition, the upper limit of the free radical polymerization initiator is preferably 20 mmol, more preferably 10 mmol, relative to 1 mol of the water-soluble ethylenically unsaturated monomer used, from the viewpoint of polymerization stability. By using the free radical polymerization initiator within this range, the production of the water-absorbent resin becomes easy.

[0053] In the polymerization step, a chain transfer agent may be used as necessary. Examples of the chain transfer agent include hypophosphites, mercaptans, thiol acids, secondary alcohols, and amines.

[0054] In the polymerization process, an internal crosslinking agent may be used as needed. Thus, the polymer obtained in the polymerization process may have a structure obtained by crosslinking the inside of the polymer using the internal crosslinking agent. Therefore, when the water-absorbent resin particles have a crosslinked structure inside the polymer, the internal crosslinked structure is formed when the water-soluble ethylenically unsaturated monomer is polymerized. In this specification, in order to distinguish it from the post-crosslinking agent described later, the crosslinking agent used in the internal crosslinking of the polymer is referred to as an internal crosslinking agent.

[0055] Examples of the internal crosslinking agent include compounds having two or more polymerizable unsaturated groups. Specific examples of the internal crosslinking agent include (poly)ethylene glycol [In this specification, for example, "polyethylene glycol" and "ethylene glycol" are collectively referred to as "(poly)ethylene glycol". The same applies to the following], di- or tri-(meth)acrylates of polyols such as (poly)propylene glycol, trimethylolpropane, glycerol polyoxyethylene glycol, polyoxypropylene glycol and (poly)glycerol; unsaturated polyesters obtained by reacting the above polyols with unsaturated acids such as maleic acid and fumaric acid; bisacrylamides such as N,N'-methylenebis(meth)acrylamide; di- or tri-(meth)acrylates obtained by reacting polyepoxide with (meth)acrylic acid; di(meth)acrylic acid carbamates obtained by reacting polyisocyanates such as toluene diisocyanate and hexamethylene diisocyanate with hydroxyethyl (meth)acrylate; allylated starch; allylated cellulose; diallyl phthalate; N,N',N"-triallyl isocyanurate; divinylbenzene, etc.

[0056] As internal crosslinking agents, in addition to the above-mentioned compounds having two or more polymerizable unsaturated groups, compounds containing glycidyl groups such as (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, and (poly)glycerol diglycidyl ether can also be listed; (poly)ethylene glycol, (poly)propylene glycol, (poly)glycerol, pentaerythritol, ethylenediamine, polyethyleneimine, (meth)glycidyl acrylate, etc. Two or more of these internal crosslinking agents can be used in combination. Among them, from the viewpoint of excellent reactivity at low temperatures, (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, (poly)glycerol diglycidyl ether and N,N'-methylenebisacrylamide are preferred.

[0057] When an internal crosslinking agent is used, the lower limit of the amount of the internal crosslinking agent used is preferably 0.0001 mmol, more preferably 0.0005 mmol, further preferably 0.001 mmol, and particularly preferably 0.01 mmol, relative to 1 mol of the water-soluble ethylenically unsaturated monomer used, from the perspective of ease of production of the water-absorbent resin. In addition, the upper limit of the amount of the internal crosslinking agent used is preferably 5 mmol, more preferably 0.5 mmol, further preferably 0.1 mmol, and particularly preferably 0.05 mmol, relative to 1 mol of the water-soluble ethylenically unsaturated monomer used. One or more types of internal crosslinking agents may be used.

[0058] In the polymerization step, the polymerization reaction temperature can be appropriately set according to the type and amount of the radical polymerization initiator, and can be set to, for example, 20 to 110° C., preferably 40 to 90° C. The reaction time can be set to, for example, 0.1 hour to 4 hours.

[0059] In the polymerization step, for example, the polymerization can be carried out in the following manner: an aqueous solution containing a water-soluble ethylenically unsaturated monomer, a thickener, a free radical polymerization initiator and an internal crosslinking agent, which has been neutralized as required, is added to a dispersion medium in which a polymer dispersion stabilizer is dissolved, and then a surfactant is added to form a suspension state. It should be noted that the order of adding the raw materials is not limited to this.

[0060] Through the above-mentioned polymerization process, the water-soluble ethylenically unsaturated monomer is polymerized to generate a polymer. For example, a slurry of a polymer in which a water-soluble ethylenically unsaturated monomer is dispersed is obtained in reverse suspension polymerization. When an internal crosslinking agent is used, the polymer obtained in the polymerization process has a structure obtained by crosslinking using the internal crosslinking agent.

[0061] In the polymerization step, in the case of the above-mentioned multi-step polymerization, the first step of reversed phase suspension polymerization can be carried out by the above-mentioned method, and then a water-soluble ethylenically unsaturated monomer is added to the reaction mixture obtained in the first step of the polymerization step and mixed, and the reversed phase suspension polymerization of the second and subsequent steps can be carried out by the same method as the first step. In the reversed phase suspension polymerization of each step after the second step, in addition to the water-soluble ethylenically unsaturated monomer, a free radical polymerization initiator and an internal crosslinking agent added as needed can be added within the range of the molar ratio of each component to the water-soluble ethylenically unsaturated monomer based on the amount of the water-soluble ethylenically unsaturated monomer added in the reversed phase suspension polymerization of each step after the second step, and the reversed phase suspension polymerization can be carried out under the same conditions as the above-mentioned method.

[0062] When reversed phase suspension polymerization is performed in multiple steps, it is preferred that the total amount of the polymerization initiator and the amount of the internal crosslinking agent used as required be within the above ranges relative to 1 mol of the water-soluble ethylenically unsaturated monomer used in the reversed phase suspension polymerization from the viewpoint of easily producing the desired water-absorbent resin.

[0063] The method for producing water-absorbent resin particles may include a drying step for drying the polymer obtained by the polymerization step. The drying step is a step for removing water from the polymer obtained by the above-mentioned polymerization step or the polymer obtained by crosslinking with an internal crosslinking agent by applying energy such as heat to the polymer from the outside. For example, in the case of reverse suspension polymerization, in the drying step, water, hydrocarbon dispersion medium, etc. can be removed from the polymer by performing azeotropic distillation in a state where the polymer (water-containing gel) obtained in the above-mentioned polymerization step is dispersed in a hydrocarbon dispersion medium. By implementing the drying step, the water content of the polymer or the polymer obtained by crosslinking with an internal crosslinking agent can be adjusted. It should be noted that the drying step can be implemented simultaneously with the post-crosslinking step described later.

[0064] The drying process may be carried out under normal pressure or under reduced pressure. In order to improve the drying efficiency, it may be carried out under a stream of nitrogen or the like. When the drying process is carried out under normal pressure, the drying temperature is preferably 70 to 250° C., more preferably 80 to 180° C., further preferably 80 to 140° C., and particularly preferably 90 to 130° C. When the drying process is carried out under reduced pressure, the drying temperature is preferably 40 to 160° C., more preferably 50 to 120° C.

[0065] The polymer obtained in the above-mentioned polymerization step (including the polymer obtained by crosslinking with an internal crosslinking agent) or the polymer obtained in the above-mentioned drying step (including the polymer obtained by crosslinking with an internal crosslinking agent) can be treated with a post-crosslinking agent. As a result, the polymer can have a structure obtained by crosslinking with a post-crosslinking agent, and the crosslinking density near the surface of the water-absorbent resin is increased. The method of treating the polymer with a post-crosslinking agent is not particularly limited, and a wide range of known methods can be used. The process of treating the polymer with a post-crosslinking agent is recorded as a "post-crosslinking process". The treatment with a post-crosslinking agent can be performed, for example, in the above-mentioned dispersion medium.

[0066] The types of post-crosslinking agents include, for example, those that can be used in conventional water-absorbent resins. The post-crosslinking agent may be a compound having two or more reactive functional groups. Specific examples of post-crosslinking agents include: polyols such as ethylene glycol, propylene glycol, 1,4-butanediol, trimethylolpropane, glycerol, polyoxyethylene glycol, polyoxypropylene glycol, and polyglycerol; polyglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)glycerol diglycidyl ether, (poly)glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, (poly)propylene glycol polyglycidyl ether, and (poly)glycerol polyglycidyl ether; epichlorohydrin, epoxypropane Halogenated epoxy compounds such as bromopropane and α-methyl epichlorohydrin; isocyanate compounds such as 2,4-toluene diisocyanate and hexamethylene diisocyanate; oxetane compounds such as 3-methyl-3-oxetane methanol, 3-ethyl-3-oxetane methanol, 3-butyl-3-oxetane methanol, 3-methyl-3-oxetane ethanol, 3-ethyl-3-oxetane ethanol, 3-butyl-3-oxetane ethanol; 1,2-ethylenedioxy Oxazoline, etc. Oxazoline compounds; carbonate compounds such as ethylene carbonate; hydroxyalkylamide compounds such as bis[N,N-di(β-hydroxyethyl)]adipamide, etc. Among them, more preferred are polyglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)ethylene glycol triglycidyl ether, (poly)glycerol diglycidyl ether, (poly)glycerol triglycidyl ether, (poly)propylene glycol polyglycidyl ether, (poly)glycerol polyglycidyl ether, etc. The post-crosslinking agent may be used alone or in combination of two or more.

[0067] The lower limit of the amount of the post-crosslinking agent used is preferably 0.01 millimole, more preferably 0.05 millimole, and further preferably 0.1 millimole relative to 1 mole of the water-soluble ethylenically unsaturated monomer constituting the post-crosslinked polymer, from the viewpoint of easily adjusting the 30-second swelling height to a specified range. In addition, the upper limit is preferably 10 millimoles, more preferably 5 millimoles, and further preferably 2 millimoles relative to 1 mole of the water-soluble ethylenically unsaturated monomer.

[0068] The reaction temperature in the post-crosslinking step (i.e., the temperature at which the polymer is treated with the post-crosslinking agent) is preferably 50 to 250° C., more preferably 60 to 180° C., and even more preferably 60 to 140° C. The reaction time for the post-crosslinking (i.e., the time for treating the polymer with the post-crosslinking agent at the reaction temperature) varies depending on the reaction temperature, the type and amount of the post-crosslinking agent used, and therefore cannot be generalized, but is generally 1 to 300 minutes, preferably 5 to 200 minutes.

[0069] In the present invention, there may be a step of adding a chelating agent described later before, during or after the post-crosslinking step. Hereinafter, this step is referred to as a "chelating agent adding step". By the chelating agent adding step, a chelating agent is added during the production process of the water-absorbent resin particles, and thus the obtained water-absorbent resin particles may contain a chelating agent. For example, a chelating agent may be arranged near the surface of the water-absorbent resin particles.

[0070] In the chelating agent adding step, for example, the chelating agent can be mixed with the polymer before post-crosslinking (i.e., before adding the post-crosslinking agent), or the chelating agent can be mixed with the polymer after post-crosslinking (i.e., after adding the post-crosslinking agent), or a combination of these can be used. That is, in the method for producing water-absorbent resin particles, the polymer can be post-crosslinked after the chelating agent is mixed with the polymer before post-crosslinking, or the chelating agent can be mixed with the polymer after the post-crosslinking. In addition, in the method for producing water-absorbent resin particles, the following steps can also be performed: the chelating agent is mixed with the polymer before post-crosslinking, then the polymer is post-crosslinked, and then the chelating agent is further mixed with the polymer after the post-crosslinking.

[0071] It should be noted that the chelating agent does not necessarily need to be added when the water-absorbent resin particles are produced, and the water-absorbent resin particles produced in advance may be mixed with the chelating agent as described later.

[0072] In the method for producing water-absorbent resin particles, additives may be added according to the purpose in order to impart various properties to the obtained water-absorbent resin particles after the polymerization step. Examples of such additives include various additives conventionally added to water-absorbent resins, such as inorganic powders, surfactants, oxidants, reducing agents, free radical chain inhibitors, antioxidants, antibacterial agents, deodorants, and the like.

[0073] The water content of the water-absorbent resin particles may be, for example, 20.0 mass % or less, 15.0 mass % or less, or 10.0 mass % or less based on the total mass of the water-absorbent resin particles. The water content based on the total mass of the water-absorbent resin particles is measured by the method described in Examples below.

[0074] (Chelating Agent)

[0075] As described above, the iron (III) chelate stability constant (logKML) of the chelate contained in the water-absorbent resin composition of the present invention is 19.0 or more and 24.0 or less. The chelate stability constant (logKML) refers to the equilibrium constant in the reaction of the metal ion and the chelate to form a chelate complex, and is an index indicating the stability of the generated chelate complex. Therefore, the iron (III) chelate stability constant (logKML) refers to the chelate stability constant in the reaction of the iron (III) ion and the chelate to form a chelate complex.

[0076] The value of the iron (III) chelate stability constant (logKML) is preferably 19.5 or more, more preferably 20.0 or more, and preferably 23.0 or less, more preferably 22.0 or less, and further preferably 21.0 or less.

[0077] As long as the iron (III) chelate stability constant (logKML) is within the above range, the types of chelating agents include, for example, ethylenediamine-N,N'-disuccinic acid (iron (III) chelate stability constant is 20.1 [logKML]), ethylene glycol bis (β-aminoethyl ether)-N,N,N,N-tetraacetic acid (iron (III) chelate stability constant is 20.5 [logKML]), 3-propylenediamine-N,N,N',N'-tetraacetic acid (iron (III) chelate stability constant is 21.6 [logKML]), pyrocatechol (iron (III) chelate stability constant is 20.4 [logKML]), N-(2-hydroxyethyl)ethylenediamine-N,N',N'-triacetic acid (iron (III) chelate stability constant is 19.8 [logKML]) and other compounds or salts thereof having an aminocarboxylic acid site.

[0078] When the chelating agent is a salt, the types of salts include, for example, alkali metal salts such as sodium and potassium; alkaline earth metal salts such as magnesium and calcium; organic amine salts, ammonium salts, etc. For the chelating agent, all or part of the ligand can form a salt. The chelating agent can be used alone, or two or more ligands can be used in combination. In the chelating agent, the number of ligands can be set to, for example, 2, 3 or 4 as the lower limit, and 12, 11 or 10 as the upper limit.

[0079] The chelating agent can be obtained by a known production method or can be obtained from a commercially available product.

[0080] (Water-absorbent resin composition)

[0081] The water-absorbent resin particles used as a basis for the content of the chelating agent may be composed of a polymer of a water-soluble ethylenically unsaturated monomer, an initiator, a crosslinking agent, and the water contained in the water-absorbent resin particles. In addition, the water-absorbent resin particles may also contain a thickener, a surfactant, and a polymer dispersant used in the polymerization process. In addition, the water-absorbent resin particles may contain various additives added after the polymerization process. Examples of additives include inorganic powders, surfactants, oxidants, reducing agents, free radical chain inhibitors, antioxidants, antibacterial agents, deodorants, and the like.

[0082] In the water-absorbent resin composition of the present invention, the content of the chelating agent can be adjusted within a range where the 30-second swelling height of the water-absorbent resin composition is 6.0 mm or more. From the viewpoint of providing the water-absorbent resin composition with excellent swelling performance, and in particular, having good decomposition performance to a degree that the water-absorbent resin composition is not easily degraded after swelling, the chelating agent is preferably contained in an amount of 0.001 to 3.00 parts by mass, more preferably 0.01 to 2.00 parts by mass, further preferably 0.05 to 1.00 parts by mass, and particularly preferably 0.10 to 0.90 parts by mass, based on 100 parts by mass of the water-absorbent resin particles.

[0083] The method for preparing the water-absorbent resin composition of the present invention can be, for example, by mixing water-absorbent resin particles and a chelating agent at a predetermined ratio to obtain the water-absorbent resin composition of the present invention. In this case, the chelating agent can be mixed with the water-absorbent resin particles in a solid state such as a powder (so-called dry mixing method), or can be mixed with the water-absorbent resin particles in a solution state dissolved in a solvent such as water.

[0084] In addition, as another method for preparing the water-absorbent resin composition of the present invention, there can be mentioned a method using the water-absorbent resin particles obtained through the above-mentioned chelating agent adding step. That is, the water-absorbent resin particles obtained through the chelating agent adding step contain water-absorbent resin particles and a chelating agent, and therefore, by using the water-absorbent resin particles obtained through the chelating agent adding step, the water-absorbent resin composition of the present invention can be prepared. For example, the water-absorbent resin particles obtained through the chelating agent adding step can be used as the water-absorbent resin composition of the present invention.

[0085] The water-absorbent resin composition of the present invention may contain other components besides the water-absorbent resin particles and the chelating agent. Examples of other components include silicon dioxide. When the water-absorbent resin composition of the present invention contains silicon dioxide, the content ratio thereof is, for example, 0.01 to 5 parts by mass, preferably 0.02 to 3 parts by mass, and more preferably 0.05 to 1 part by mass relative to 100 parts by mass of the water-absorbent resin particles. The water-absorbent resin composition of the present invention may contain other components besides silicon dioxide, and examples thereof include various components contained in known water-stopping materials.

[0086] The water-absorbent resin composition of the present invention preferably contains 50% by mass or more of the water-absorbent resin particles and the chelating agent, more preferably 80% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass or more. The water-absorbent resin composition of the present invention may consist only of the water-absorbent resin particles and the chelating agent, or may consist only of the water-absorbent resin particles, the chelating agent, and silica.

[0087] The median particle size of the water-absorbent resin composition of the present invention is, for example, 10 to 500 μm, preferably 30 to 300 μm, more preferably 50 to 250 μm, and even more preferably 100 to 200 μm from the viewpoint that the 30-second swelling height described later is easily within a desired range. The water-absorbent resin of the present invention may be in various shapes, for example, spherical, crushed, granular, ellipsoidal, scaly, rod-like, blocky, and the like.

[0088] As described above, the 30-second swelling height of the water-absorbent resin composition of the present invention is 6.0 mm or more. Therefore, the water-absorbent resin composition of the present invention can impart excellent swelling performance to the water-stop material. The 30-second swelling height of the water-absorbent resin composition of the present invention can be measured according to the measurement method described in the section of the embodiment. The 30-second swelling height of the water-absorbent resin composition can be adjusted by appropriately selecting the type of water-absorbent resin particles, the median particle size, and the type of chelating agent.

[0089] The 30-second swelling height of the water-absorbent resin composition of the present invention is preferably 8.0 mm or more, more preferably 10.0 mm or more, and even more preferably 12.0 mm or more. The upper limit of the 30-second swelling height may be 26.0 mm or 18.0 mm.

[0090] The water-stopping rate of the water-absorbent resin composition of the present invention is preferably 25% or more. In this case, the water-absorbent resin composition has high water-stopping performance, and can maintain the gel state for a long time even in the use environment of power cables or similar environments. The water-stopping rate of the water-absorbent resin composition of the present invention is more preferably 25 to 60%, further preferably 30 to 50%, and particularly preferably 30 to 45%.

[0091] The gel viscosity retention rate S of the water-absorbent resin composition of the present invention is preferably 0 to 20%. In this case, the water-absorbent resin composition has a property of being easily decomposed, for example, relatively easily decomposed even when released into the natural world. The gel viscosity retention rate S of the water-absorbent resin composition of the present invention is more preferably 0 to 10%, and further preferably 0 to 5%. It should be noted that the gel viscosity retention rate S of the water-absorbent resin composition of the present invention can be calculated according to the measurement method described in the "Measurement of gel viscosity retention rate" of the Examples.

[0092] The gel viscosity of the water-absorbent resin composition of the present invention after 18 days is preferably 2000 mPa·s or less. In this case, the decomposition performance of the water-absorbent resin composition is excellent. The gel viscosity of the water-absorbent resin composition of the present invention after 18 days is more preferably 1500 mPa·s or less, further preferably 1000 mPa·s or less, and particularly preferably 900 mPa·s or less.

[0093] The water-absorbent resin composition of the present invention has excellent swelling performance and has the property of not being easily degraded by heat or the like after swelling, so it has excellent water-stopping performance. In addition, the water-absorbent resin composition of the present invention has the property of not being easily degraded and has excellent decomposition performance, so even if the water-absorbent resin flows out into the natural world, the impact on the environmental load is small. Therefore, the water-absorbent resin composition of the present invention is suitable for various uses, for example, it can be widely used in various fields such as industrial materials such as water-stopping materials and anti-condensation agents, agricultural and horticultural materials such as water-retaining agents and soil improvers, and sanitary materials such as diapers and sanitary products. In particular, the water-absorbent resin of the present invention can maintain the water-stopping effect for a long time, so it is suitable for use in water-stopping materials.

[0094] [Evaluation of water-absorbent resin particles]

[0095] Unless otherwise specified, the measurements were performed under an environment of a temperature of 25±2° C. and a humidity of 50±10%.

[0096] (Determination of moisture content)

[0097] Place 2.0 g of water-absorbent resin particles in an aluminum foil box that is pre-set to a constant weight (W1 (g)), gently close the mouth of the aluminum foil box, and accurately weigh the total mass W2 (g) of the aluminum foil box containing the sample. Use a hot air dryer set at an internal temperature of 200°C to dry the aluminum foil box containing the sample for 2 hours. Cool the dried aluminum foil box containing the sample in a dryer to room temperature. Measure the total mass W3 (g) of the aluminum foil box containing the sample after cooling. Calculate the moisture content of the sample by the following formula.

[0098] Moisture content [mass %] = {(W2-W3) / (W2-W1)} × 100

[0099] [Evaluation of water-absorbent resin composition]

[0100] Unless otherwise specified, the measurements were performed under an environment of a temperature of 25±2° C. and a humidity of 50±10%.

[0101] (Measurement of median particle size (particle size distribution))

[0102] 5 g of the water-absorbent resin composition was sieved using a sonic vibration sieve measuring device (Robot Shifter), sieves with mesh sizes of 850 μm, 500 μm, 250 μm, 180 μm, 150 μm, 106 μm and 75 μm according to the JIS standard, and a tray. The mass of the particles remaining on each sieve was calculated as a mass percentage relative to the total amount. The mass percentage of the particles remaining on each sieve was accumulated in order from the particles with the largest particle size, and the relationship between the mesh size of the sieve and the cumulative value of the mass percentage of the particles remaining on the sieve was plotted on a logarithmic probability paper. The particle size corresponding to the cumulative mass percentage of 50% was obtained by connecting the scattered points on the probability paper with a straight line, and it was taken as the median particle size of the water-absorbent resin composition.

[0103] (30-second swelling height measurement)

[0104] use Figure 1 The swelling height measuring device X shown measures the swelling height of the water-absorbent resin composition. Figure 1 The swelling height measuring device X shown in the figure comprises a moving distance measuring device 1, a concave circular cup 2 (45 mm in height, 90 mm in outer diameter, 40 mm in depth of the concave portion, 80 mm in inner diameter of the concave portion), a plastic convex circular cylinder 3 (79 mm in outer diameter, 60 through holes 7 with a diameter of 2 mm evenly arranged on the contact surface with the water-absorbent resin composition), and a nonwoven fabric 4 (weight per unit area 11 g / m 2 The swelling height measuring device X can measure the displacement of the distance moved by the convex circular cylinder 3 in units of 0.01 mm using the laser 6. The concave circular cup 2 can evenly spread a predetermined amount of the water-absorbent resin composition. The convex circular cylinder 3 can evenly apply a load of 90 g to the water-absorbent resin composition 5 as a sample.

[0105] First, 0.2 g of the sample (water-absorbent resin composition 5) is uniformly spread in the concave circular cup 2, and a nonwoven fabric 4 is laid on it. Then, the convex circular cylinder 3 is gently placed on the nonwoven fabric 4, and the laser 6 of the sensor of the moving distance measuring device 1 is set to reach the center of the cylinder 3. Ion exchange water adjusted to 20° C. in advance is poured into the concave circular cup 2 through the through hole 7 of the convex circular cylinder 3 to swell the water-absorbent resin composition 5. The time when the laser senses that the water-absorbent resin composition 5 is swollen and the convex circular cylinder 3 is pushed up is regarded as the start of water absorption (0 seconds) (automatic measurement starts when a displacement of 0.5 mm occurs), and the distance (the displacement difference of the convex circular cylinder 3 in the direction perpendicular to the bottom surface of the concave part of the concave circular cup 2) by which the water-absorbent resin composition 5 is swollen and the convex circular cylinder 3 is pushed up is measured. The water level of the ion exchanged water was checked every 3 seconds from the start of the injection of the ion exchanged water, and the injection of the ion exchanged water was continued intermittently so that the water surface was maintained at a height near the flat surface of the flat plate portion of the convex circular cylindrical body 3. 30 seconds after the moment when the water-absorbent resin composition 5 started to absorb water (more precisely, the moment when the water-absorbent resin composition absorbed a very small amount of ion exchanged water and the cylindrical body 3 was pushed up by 0.5 mm), the distance by which the convex circular cylindrical body 3 was pushed up (including the height (0.5 mm) by which the cylindrical body 3 was pushed up at the moment when the water absorption started) was recorded as the 30-second swelling height.

[0106] (Measurement of gel viscosity retention rate)

[0107] The gel viscosity of the water-absorbent resin composition was measured by adjusting the temperature of the swollen gel to 25±0.5° C. using a Brookfield type rotational viscometer (type A, spindle rotor No. 5, rotation speed 10 rpm). The gel viscosity was measured in a state where the gel was placed in a 200 mL glass beaker with an inner diameter of 64 mmφ to a height of 65 mm.

[0108] Add 1500g of ion exchange water to a 2L beaker and stir at 600rpm using a magnetic stirring bar. Add 1.5g of the water-absorbent resin composition into the vortex generated by the stirring, and then stir for 1 hour. Then, filter using a sieve with a mesh of 75μm and let it stand for 30 minutes. Immediately measure the gel viscosity of the swollen gel obtained in this way as the "initial gel viscosity". The swollen gel after the measurement is immediately placed in a 250mL glass heat-resistant bottle with a bottom shape of 70mmφ and a mouth shape of 42mmφ, and let it stand in a hot air dryer at 50±2℃. After 18 days, measure the viscosity of the swollen gel, and calculate the gel viscosity retention rate S from the value of the gel viscosity after 18 days by the following formula (I).

[0109] Gel viscosity retention rate S = B / A (I)

[0110] (In formula (I), A represents the initial gel viscosity (mPa·s), and B represents the gel viscosity after 18 days (mPa·s))

[0111] (Determination of water stop rate)

[0112] use Figure 2 The measuring device shown is used to evaluate the water-stopping performance of the water-absorbent resin composition. Figure 2 The measuring device shown is formed by a cylindrical container 8 made of acrylic resin (hereinafter, recorded as cylindrical container (A)), a cylindrical container 9 made of acrylic resin (hereinafter, recorded as cylindrical container (B)) and a swollen water-absorbent resin composition 15. A nylon mesh (250 mesh) 11 having the same size as the outer diameter of the cylindrical container (A) is bonded to the bottom of the cylindrical container (A). The cylindrical container (A) has an inner diameter of 20 mm, an outer diameter of 25 mm, a height of 120 mm, and a weight of 31 g. A nylon mesh (250 mesh) 10 having the same size as the outer diameter of the cylindrical container (B) is bonded to the bottom of the cylindrical container (B). The inner diameter of the cylindrical container (B) is 26 mm, the outer diameter is 38 mm, and the height is 120 mm. The cylindrical container (A) is configured to be able to move up and down without resistance inside the cylindrical container (B). 0.20 g of the water-absorbent resin composition was uniformly added to the cylindrical container (B), and then the cylindrical container (A) was inserted into the cylindrical container (B) from the top to form a measuring portion.

[0113] A metal mesh 14 with a mesh size of 1.8 mm (50 mm×50 mm) was placed at the bottom of a petri dish 13 having an inner diameter of 90 mm and a depth of 15 mm and containing 50 g of ion exchange water 12. The nylon mesh sheet 10 side of the measurement part was placed on the metal mesh 14, thereby swelling the water-absorbent resin composition 15 in the measurement part for 30 minutes, and the swollen gel formed was collected in a 250 mL glass heat-resistant bottle having an outer shape of 70 mmφ at the bottom and an outer shape of 42 mmφ at the mouth. The same operation as the above operation was repeated again to form a swollen gel, which was collected in the same glass heat-resistant bottle as the first time, and a swollen gel corresponding to 0.40 g of the water-absorbent resin composition before swelling was obtained. The glass heat-resistant bottle was placed in a hot air dryer at 90±2°C and heated for 42 hours. The heated gel was returned to room temperature, and then the entire amount of the gel was transferred to a 500 mL beaker, and ion exchange water was added to adjust the total amount (the entire amount of the gel and the ion exchange water) to 400 g. The mixture was stirred at 600 rpm for 1 hour using a magnetic stirring bar, and then filtered through a sieve with a mesh size of 75 μm to recover the filtrate. The obtained filtrate was further suction filtered using a Kiriyama funnel (filter paper: ADVANTEC, No. 6) to recover the filtrate.

[0114] 50 g of the filtrate obtained as above was taken into a weighed 100 mL beaker which was previously kept constant at 140° C. The filtrate in the beaker was heated in a hot air dryer at 140° C. for 15 hours to remove moisture, and the mass W (g) of the remaining solid content was measured. The water-stopping performance was quantified by the following formula (II) to evaluate the water-stopping rate.

[0115] Water stop rate (%) = [1-(W / 50) × 400 / 0.4] × 100 (II)

[0116] 2. Water-stop materials and cables

[0117] As long as the water-absorbing resin composition of the present invention is provided, the composition of the water-absorbing resin composition of the present invention may be the same as that of a known water-absorbing resin composition. The water-absorbing resin composition may be formed by the water-absorbing resin composition alone. Alternatively, the water-absorbing resin composition may be formed by molding a mixture with rubber and / or a thermoplastic resin. In addition, the water-absorbing resin composition of the present invention may be retained on a nonwoven fabric or paper to form a water-absorbing resin. Examples of the water-absorbing resin composition include water-absorbing tapes, water-absorbing yarns, and the like.

[0118] The water stop can be obtained, for example, by holding the water-absorbent resin composition on a liquid-permeable sheet. Alternatively, the water stop can be obtained by sandwiching the water-absorbent resin composition between two or more liquid-permeable sheets. Specifically, an adhesive can be used to adhere the water-absorbent resin composition to a liquid-impermeable sheet to form a sheet, thereby obtaining a water stop. As the liquid-permeable sheet, for example, non-woven fabrics, woven fabrics, films, etc. made of synthetic resins such as polyolefins, polyesters, polyamides, nylons, and acrylics can be used.

[0119] The water-stop yarn can be obtained, for example, by coating the water-absorbent resin composition of the present invention on a substrate or impregnating the substrate. The substrate may be a long fiber or plastic yarn (substrate yarn) of a synthetic fiber, specifically, a long fiber or plastic yarn of a synthetic resin such as polyolefin, polyester, polyamide, nylon, or acrylic.

[0120] In the production of the water-stop yarn, the method of applying the water-absorbent resin composition to the substrate or impregnating the substrate is not particularly limited. For example, a dispersion obtained by dispersing the water-absorbent resin composition in an organic solvent may be applied to the substrate or impregnated into the substrate, thereby causing the water-absorbent resin composition to adhere to the substrate. In the case where the water-absorbent resin composition has weak adhesion to the substrate, an adhesive may be used in combination to improve adhesion.

[0121] Examples of the above-mentioned adhesives include: rubber-based adhesives such as natural rubber, butyl rubber, and polyisoprene; styrene-based elastomer adhesives such as styrene-isoprene block copolymers (SIS) and styrene-butadiene block copolymers (SBS); ethylene-vinyl acetate copolymer (EVA) adhesives; ethylene-ethyl acrylate copolymers (EEA) and other ethylene-acrylic acid derivative copolymer-based adhesives; ethylene-acrylic acid copolymer (EAA) adhesives; polyamide-based adhesives such as copolymerized nylon; polyolefin-based adhesives such as polyethylene and polypropylene; polyester-based adhesives such as polyethylene terephthalate (PET) and copolymerized polyesters, and acrylic adhesives.

[0122] The waterproof material of the present invention comprises the water-absorbing resin composition of the present invention and therefore has excellent heat resistance. In particular, even if the waterproof material absorbs water and gels and is left in a high temperature environment, the gel is unlikely to deteriorate and the waterproof performance is unlikely to decrease.

[0123] The water-stopping material of the present invention can be applied to various purposes, such as optical cables and other communication cables and various cables such as power cables, and can be used in particular for power cables used underground and under the sea. In particular, the water-stopping tape, water-stopping yarn, etc. are particularly suitable as water-stopping materials for power cables.

[0124] As a power cable, as long as it has the above-mentioned water-stopping material, its structure is not particularly limited, and for example, it can be set to the same structure as the known power cable. Like a general power cable, it can have a structure in which an inner semiconductive layer, an insulating layer, an outer semiconductive layer, and a coating layer are sequentially arranged on the outer periphery of the central conductor. In order to prevent water intruding from the outside from traveling along the length direction of the cable, a waterstop is arranged between the outer semiconductive layer and the coating. In addition, the waterstop can be arranged between the inner semiconductive layer and the insulating layer. In addition, a waterstop yarn can also be accommodated in the central conductor.

[0125] When determining the invention included in the present invention, each configuration (property, structure, function, etc.) described in each embodiment of the present invention can be arbitrarily combined. That is, the present invention includes all the themes consisting of all combinations of the configurations that can be combined as described in this specification.

[0126] Example

[0127] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples. It should be noted that the water-absorbent resin particles obtained in the following production examples and the water-absorbent resin compositions obtained in the examples and comparative examples were evaluated by various test methods described below. Unless otherwise specified, the measurements were performed under an environment of a temperature of 25±2°C and a humidity of 50±10%.

[0128] [Manufacturing of water-absorbent resin particles]

[0129] (Production Example 1)

[0130] A round-bottomed cylindrical separable flask with an inner diameter of 11 cm and a capacity of 2 L, equipped with a reflux condenser, a dropping funnel, a nitrogen inlet tube, and a stirring blade having four inclined blades with a blade diameter of 5 cm in two stages as a stirrer, was prepared. 292 g of n-heptane as a hydrocarbon dispersion medium was measured into the flask, 0.782 g of maleic anhydride-modified ethylene-propylene copolymer (Mitsui Chemicals, Inc., HI-WAX1105A) as a polymer dispersant was added, and the temperature was raised to 80° C. while stirring to dissolve the dispersant, and then cooled to 56° C. On the other hand, 92.0 g (1.03 mol) of an 80.5% by mass acrylic acid aqueous solution as a water-soluble ethylenically unsaturated monomer was measured into a beaker with an internal volume of 300 mL, and 102.8 g of a 30% by mass sodium hydroxide aqueous solution was added dropwise while cooling with ice water to prepare a 75 mol % neutralized product of acrylic acid. 44.7 g of water, 0.0644 g (0.238 mmol) of potassium persulfate as a water-soluble radical polymerization agent, and 0.0102 g (0.059 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were further added and dissolved to prepare an aqueous liquid for the first step. The aqueous liquid was added to a separable flask and stirred for 10 minutes, and then a surfactant solution of 0.782 g of HLB3 sucrose stearate (Mitsubishi Chemical Foods Co., Ltd., Ryoto Sucrose Ester S-370) dissolved in 7.04 g of n-heptane as a surfactant was further added to a 20 mL-tube bottle, and the rotation speed of the stirrer was set to 450 rpm. While stirring, the system was fully replaced with nitrogen, and then the flask was immersed in a 70°C water bath to increase the temperature, and polymerization was carried out for 60 minutes, thereby obtaining a polymerization slurry for the first step.

[0131] On the other hand, 101.2 g (1.13 mol) of an 80.5% by mass acrylic acid aqueous solution as a water-soluble ethylenically unsaturated monomer was weighed into another beaker having an internal volume of 500 mL, and while cooling with ice water, 113.1 g of a 30% by mass sodium hydroxide aqueous solution was added dropwise to prepare a 75 mol % neutralized product of acrylic acid. Further, 13.2 g of water, 0.081 g (0.300 mmol) of potassium persulfate as a water-soluble free radical polymerization agent, and 0.0092 g (0.053 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were added and dissolved to prepare an aqueous liquid for the second step.

[0132] The rotation speed of the stirrer was set to 1000 rpm, and the inside of the separable flask was cooled to 31°C while stirring. Then, the entire amount of the aqueous liquid in the second step was added to the polymerization slurry in the first step, and the inside of the system was replaced with nitrogen for 30 minutes. Then, the flask was immersed in a water bath at 70°C to raise the temperature, and a polymerization reaction was carried out for 60 minutes to obtain a hydrogel polymer 1. Then, the flask was immersed in an oil bath set at 125°C, and 243.2 g of water was discharged to the outside of the system by azeotropic distillation of n-heptane and water while refluxing n-heptane. Then, 7.15 g (0.821 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a post-crosslinking agent was added to the flask, and the mixture was kept at 83°C for 2 hours. Next, the n-heptane was heated in an oil bath at 125°C to evaporate and dry, and then passed through a sieve with a mesh size of 850 μm, thereby obtaining 196.5 g of water-absorbent resin particles (1). The water content of the water-absorbent resin particles (1) was 4.6% by mass.

[0133] (Production Example 2)

[0134] A round-bottomed cylindrical separable flask with an inner diameter of 11 cm and a capacity of 2 L, equipped with a reflux condenser, a dropping funnel, a nitrogen inlet tube, and a stirring blade (a fluororesin is coated on the surface) having four inclined paddle blades with a blade diameter of 5 cm in two stages as a stirrer, was prepared. 471 g of n-heptane as a hydrocarbon dispersion medium was added to the flask, and 1.10 g of HLB8.6 sorbitan monolaurate (manufactured by NOF Corporation, trade name NONION LP-20R) was added as a surfactant, and the temperature was raised to 46° C. On the other hand, 92.0 g (1.03 mol) of an 80.5% by mass acrylic acid aqueous solution as a water-soluble ethylenically unsaturated monomer was measured into a beaker with an internal volume of 300 mL, and 102.8 g of a 30% by mass sodium hydroxide aqueous solution was added dropwise while cooling with ice water to prepare a 75 mol % neutralized product of acrylic acid. 44.6 g of water and 0.1012 g (0.374 mmol) of potassium persulfate as a water-soluble radical polymerization agent were further added and dissolved to prepare an aqueous liquid. The aqueous liquid was added to a separable flask, the rotation speed of the stirrer was set to 700 rpm, and the inside of the flask was replaced with nitrogen for 30 minutes while stirring. Then, the flask was immersed in a 70°C water bath to increase the temperature, and polymerization was performed for 60 minutes to obtain a hydrogel polymer 2.

[0135] After the polymerization, 0.41 g (0.047 mmol) of a 2% aqueous solution of ethylene glycol diglycidyl ether was added to the flask. Next, the flask was immersed in an oil bath set at 125°C, and 103.3 g of water was discharged to the outside of the system by azeotropic distillation of n-heptane and water while refluxing the n-heptane. Then, 2.76 g (0.317 mmol) of a 2% aqueous solution of ethylene glycol diglycidyl ether as a post-crosslinking agent was added to the flask and kept at 83°C for 2 hours. Then, the n-heptane was heated in an oil bath at 125°C to evaporate and dry, and further passed through a sieve with a mesh size of 850 μm, thereby obtaining 68.0 g of water-absorbent resin particles (2). The water content of the water-absorbent resin particles (2) was 3.5% by mass.

[0136] (Production Example 3)

[0137] A round-bottomed cylindrical separable flask with an inner diameter of 11 cm and a capacity of 2 L, equipped with a reflux condenser, a dropping funnel, a nitrogen inlet tube, and a stirring blade having four inclined paddle blades with a blade diameter of 5 cm in two stages as a stirrer, was prepared. 293 g of n-heptane as a hydrocarbon dispersion medium was measured into the flask, 0.736 g of maleic anhydride-modified ethylene-propylene copolymer as a polymer dispersant was added, and the temperature was raised to 80° C. while stirring to dissolve the dispersant, and then cooled to 60° C. On the other hand, 92.0 g (1.03 mol) of an 80.5% by mass acrylic acid aqueous solution was measured into a beaker with an internal volume of 300 mL, and 102.8 g of a 30% by mass sodium hydroxide aqueous solution was added dropwise while cooling with ice water to prepare a 75 mol % neutralized product of acrylic acid. 44.6 g of water, 0.0736 g (0.272 mmol) of potassium persulfate as a water-soluble free radical polymerization agent, and 0.010 g (0.059 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were further added and dissolved to prepare an aqueous liquid for the first step. The aqueous liquid was added to a separable flask and stirred for 10 minutes, and then a surfactant solution of 0.736 g of HLB3 sucrose stearate dissolved in 6.62 g of n-heptane by heating was further added to a 20 mL-tube bottle, and the rotation speed of the stirrer was set to 500 rpm. While stirring, the system was fully replaced with nitrogen, and then the flask was immersed in a 68°C water bath to raise the temperature, and polymerization was carried out for 60 minutes, thereby obtaining a polymerization slurry for the first step.

[0138] On the other hand, 128.8 g (1.44 mol) of an 80.5% by mass aqueous solution of acrylic acid as a water-soluble ethylenically unsaturated monomer was weighed into another beaker having an internal volume of 500 mL, and while cooling with ice water, 143.9 g of a 30% by mass aqueous solution of sodium hydroxide was added dropwise to prepare a 75 mol% neutralized product of acrylic acid. Further, 16.8 g of water, 0.103 g (0.381 mmol) of potassium persulfate as a water-soluble free radical polymerization agent, and 0.0116 g (0.067 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were added and dissolved to prepare an aqueous liquid for the second step.

[0139] The rotation speed of the stirrer was set to 1000 rpm, and the inside of the separable flask was cooled to 28°C while stirring. Then, the entire amount of the aqueous liquid in the second step was added to the polymerization slurry in the first step, and the inside of the system was replaced with nitrogen for 30 minutes. Then, the flask was immersed in a water bath at 70°C to raise the temperature, and a polymerization reaction was carried out for 60 minutes to obtain a hydrogel polymer 3. Then, the flask was immersed in an oil bath set at 125°C, and 258.5 g of water was discharged to the outside of the system by azeotropic distillation of n-heptane and water while refluxing n-heptane. Then, 4.42 g (0.507 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a post-crosslinking agent was added to the flask, and the mixture was kept at 83°C for 2 hours. Next, the n-heptane was heated in an oil bath at 125°C to evaporate and dry, and then passed through a sieve with a mesh size of 850 μm, thereby obtaining 221.4 g of water-absorbent resin particles (3). The water content of the water-absorbent resin particles (3) was 5.4% by mass.

[0140] [Production of water-absorbent resin composition]

[0141] (Example 1)

[0142] 0.1 parts by mass of amorphous silica (Tokusil NP-S, Oriental Silicas Corporation) was mixed with 100 parts by mass of the water-absorbent resin particles (1) obtained in Production Example 1. 0.58 parts by mass of ethylenediamine-N,N'-disuccinic acid trihydrate (hereinafter referred to as EDDS·4H·3H2O) having an iron (III) chelating stability constant of 20.1 [logKML] as a chelating agent (hereinafter referred to as EDDS·4H·3H2O) was added in a powder state (17 μmol of EDDS·4H·3H2O per 1 g of the water-absorbent resin particles) and mixed thoroughly to obtain a water-absorbent resin composition (1). The median particle size of the water-absorbent resin composition (1) was 179 μm, and the 30-second swelling height was 8.9 mm.

[0143] It should be noted that the iron (III) chelation stability constant of EDDS·4H·3H2O is a value obtained by referring to “Isabel S.S. Pinto, Isabel FF Neto, Helena MVM Soares. 2014. Biodegradable chelating agents for industrial, domestic, and agricultural applications-a review. Environ Sci Pollut Res. 21.11893-11906.”

[0144] (Example 2)

[0145] A water-absorbent resin composition (2) was obtained by the same method as in Example 1 except that 0.76 parts by mass (20 μmol of GEDTA·4H per 1 g of water-absorbent resin particles) of ethylene glycol bis(β-aminoethyl ether)-N,N,N,N-tetraacetic acid (hereinafter, abbreviated as GEDTA·4H) having an iron (III) chelating stability constant of 20.5 [logKML] was used instead of EDDS·4H·3H2O. The median particle size of the water-absorbent resin composition (2) was 179 μm, and the 30-second swelling height was 9.2 mm.

[0146] It should be noted that the iron (III) chelation stability constant of GEDTA·4H refers to the value of "Tongren Chemical. 2018. Product Catalog. 31st Edition. 268-269."

[0147] (Example 3)

[0148] 0.58 parts by mass (17 μmol of EDDS·4H·3H2O per 1 g of the water-absorbent resin particles) of EDDS·4H·3H2O as a chelating agent was added in a powder state to 100 parts by mass of the water-absorbent resin particles (2) obtained in Production Example 2, and the mixture was thoroughly mixed to obtain a water-absorbent resin composition (3). The median particle size of the water-absorbent resin composition (3) was 166 μm, and the 30-second swelling height was 14.7 mm.

[0149] (Example 4)

[0150] A water-absorbent resin composition (4) was obtained by the same method as in Example 3 except that 0.76 parts by mass (20 μmol of GEDTA·4H per 1 g of water-absorbent resin particles) of GEDTA·4H was used as a chelating agent instead of EDDS·4H·3H2O. The median particle size of the water-absorbent resin composition (4) was 166 μm, and the 30-second swelling height was 13.6 mm.

[0151] (Example 5)

[0152] A water-absorbent resin composition (5) was obtained by the same method as in Example 1 except that the amount of EDDS·4H·3H2O used was changed to 0.01 parts by mass (0.29 μmol of EDDS·4H·3H2O per 1 g of water-absorbent resin particles). The median particle size of the water-absorbent resin composition (5) was 179 μm, and the 30-second swelling height was 8.5 mm.

[0153] (Example 6)

[0154] A water-absorbent resin composition (6) was obtained by the same method as in Example 1 except that the amount of EDDS·4H·3H2O used was changed to 0.1 parts by mass (2.9 μmol of EDDS·4H·3H2O per 1 g of water-absorbent resin particles). The median particle size of the water-absorbent resin composition (6) was 179 μm, and the 30-second swelling height was 8.7 mm.

[0155] (Example 7)

[0156] A water-absorbent resin composition (7) was obtained by the same method as in Example 1 except that the amount of EDDS·4H·3H2O used was changed to 2.0 parts by mass (58 μmol of EDDS·4H·3H2O per 1 g of water-absorbent resin particles). The median particle size of the water-absorbent resin composition (7) was 179 μm, and the 30-second swelling height was 8.0 mm.

[0157] (Example 8)

[0158] A water-absorbent resin composition (8) was obtained by the same method as in Example 1 except that the amount of EDDS·4H·3H2O used was changed to 3.0 parts by mass (87 μmol of EDDS·4H·3H2O per 1 g of water-absorbent resin particles). The median particle size of the water-absorbent resin composition (8) was 179 μm, and the 30-second swelling height was 7.6 mm.

[0159] (Example 9)

[0160] A slurry containing the hydrogel polymer 1 was prepared by the same method as in Production Example 1. The flask containing the slurry containing the hydrogel polymer 1 was immersed in an oil bath set at 125° C., and 246.0 g of water was discharged to the outside of the system by azeotropic distillation of n-heptane and water while refluxing the n-heptane, and 4.31 g of a 35% by mass aqueous solution of ethylenediamine-N,N'-disuccinic acid·trisodium salt (hereinafter abbreviated as EDDS·3Na) was added (21 μmol of EDDS·3Na per 1 g of water-absorbent resin particles). Then, 7.15 g (0.821 mmol) of a 2% by mass aqueous solution of ethylene glycol diglycidyl ether as a post-crosslinking agent was added to the flask, and the mixture was kept at 83° C. for 2 hours. Next, the n-heptane was heated in an oil bath at 125° C. to evaporate and dry, thereby obtaining 197.8 g of water-absorbent resin particles. The mixture was further passed through a sieve with a mesh size of 850 μm, thereby obtaining 197.3 g of water-absorbent resin particles (4). The water content of the water-absorbent resin particles (4) was 3.3% by mass. With respect to 100 parts by mass of the water-absorbent resin particles (4), 0.1 parts by mass of amorphous silica (Oriental Silicas Corporation, Tokusil NP-S) was mixed, thereby obtaining a water-absorbent resin composition (9). The median particle size of the water-absorbent resin composition (9) was 172 μm, and the 30-second swelling height was 8.9 mm.

[0161] (Example 10)

[0162] A slurry containing a hydrogel polymer 2 was prepared by the same method as in Production Example 2. The flask containing the slurry containing the hydrogel polymer 1 was immersed in an oil bath set at 125°C, and 104.8 g of water was discharged to the outside of the system by azeotropic distillation of n-heptane and water while refluxing the n-heptane, and 2.25 g of a 35% by mass EDDS·3Na aqueous solution (23 μmol of EDDS·3Na per 1 g of water-absorbent resin particles) was added. Then, 2.76 g (0.317 mmol) of a 2% by mass ethylene glycol diglycidyl ether aqueous solution as a post-crosslinking agent was added to the flask, and the mixture was kept at 83°C for 2 hours. Then, the n-heptane was heated in an oil bath at 125°C, evaporated, and dried to obtain 95.3 g of water-absorbent resin particles. The mixture was further passed through a sieve with a mesh size of 850 μm to obtain 69.2 g of a water-absorbent resin composition (10). The water content of the water-absorbent resin composition (10) was 3.2% by mass, the median particle size was 219 μm, and the 30-second swelling height was 15.6 mm.

[0163] (Comparative Example 1)

[0164] A water-absorbent resin composition (11) was obtained by the same method as in Example 1 except that 0.46 parts by mass of L-(+)-tartrate disodium dihydrate (20 μmol of L-(+)-tartrate disodium dihydrate per 1 g of water-absorbent resin particles) having an iron (III) chelating stability constant of 18.1 [logKML] was used as a chelating agent instead of EDDS·4H·3H2O. The median particle size of the water-absorbent resin composition (11) was 179 μm, and the swelling height after 30 seconds was 8.6 mm. It should be noted that the iron (III) chelating stability constant of L-(+)-tartrate disodium dihydrate is a value obtained by referring to "Takashi Minoura. 1984. On the Chelating Agent Industry. Organic Synthetic Chemistry. 42 (2). 165-169."

[0165] (Comparative Example 2)

[0166] A water-absorbent resin composition (12) was obtained by the same method as in Example 1 except that 0.6 parts by mass of ethylenediaminetetraacetic acid (hereinafter abbreviated as EDTA·4H) having an iron (III) chelating stability constant of 25.1 [logKML] (21 μmol of EDTA·4H per 1 g of water-absorbent resin particles) was used as a chelating agent instead of EDDS·4H·3H2O. The median particle size of the water-absorbent resin composition (12) was 179 μm, and the 30-second swelling height was 8.7 mm.

[0167] It should be noted that the iron (III) chelation stability constant of EDTA·4H refers to the value of "Tongren Chemical. 2018. Product Catalog. 31st Edition. 268-269."

[0168] (Comparative Example 3)

[0169] A water-absorbent resin composition (13) was obtained by the same method as in Example 1 except that 0.8 parts by mass (20 μmol of DTPA·5H per 1 g of water-absorbent resin particles) of diethylenetriaminepentaacetic acid (hereinafter abbreviated as DTPA·5H) having an iron (III) chelating stability constant of 28.6 [logKML] was used instead of EDDS·4H·3H2O. The median particle size of the water-absorbent resin composition (13) was 179 μm, and the 30-second swelling height was 9.2 mm.

[0170] It should be noted that the iron (III) chelation stability constant of DTPA·5H refers to the value of “Tongren Chemical. 2018. Product Catalog. 31st Edition. 268-269.”

[0171] (Comparative Example 4)

[0172] A water-absorbent resin composition (14) was obtained by the same method as in Example 3 except that 0.6 parts by mass of EDTA·4H (21 μmol of EDTA·4H per 1 g of water-absorbent resin particles) was used as a chelating agent instead of EDDS·4H·3H2O. The median particle size of the water-absorbent resin composition (14) was 166 μm, and the 30-second swelling height was 14.5 mm.

[0173] (Comparative Example 5)

[0174] A water-absorbent resin composition (15) was obtained in the same manner as in Example 1 except that the water-absorbent resin particles (1) were changed to the water-absorbent resin particles (3) obtained in Production Example 3. The median particle size of the water-absorbent resin composition (15) was 344 μm, and the 30-second swelling height was 4.8 mm.

[0175] [Evaluation of water-absorbent resin particles]

[0176] (Determination of moisture content)

[0177] 2.0 g of water-absorbent resin particles are placed in an aluminum foil box (No. 8) that is pre-set to a constant weight (W1 (g)), the opening of the aluminum foil box is gently closed, and the total mass W2 (g) of the aluminum foil box containing the sample is accurately weighed. The aluminum foil box containing the sample is dried for 2 hours using a hot air dryer (manufactured by ADVANTEC, model: FV-320) with the internal temperature set to 200°C. The dried aluminum foil box containing the sample is cooled to room temperature in a desiccator. The total mass W3 (g) of the aluminum foil box containing the sample after cooling is measured. The moisture content of the sample is calculated by the following formula.

[0178] Moisture content [mass %] = {(W2-W3) / (W2-W1)} × 100

[0179] [Evaluation of water-absorbent resin composition]

[0180] (Measurement of median particle size (particle size distribution))

[0181] 5 g of the water-absorbent resin particles obtained in each manufacturing example were sieved using a sonic vibration sieve measuring device (Robot Shifter RPS-01, manufactured by Shinshin Enterprise Co., Ltd.), sieves with mesh sizes of 850 μm, 500 μm, 250 μm, 180 μm, 150 μm, 106 μm and 75 μm according to the JIS standard, and a tray. The mass of the particles remaining on each sieve was calculated as a mass percentage relative to the total amount. The mass percentage of the particles remaining on each sieve was accumulated in sequence starting from the particles with the largest particle size, and the relationship between the mesh size of the sieve and the cumulative value of the mass percentage of the particles remaining on the sieve was plotted on a logarithmic probability paper. By connecting the scattered points on the probability paper with a straight line, the particle size equivalent to the cumulative mass percentage of 50% was obtained, which was used as the median particle size of the water-absorbent resin particles.

[0182] (30-second swelling height measurement)

[0183] use Figure 1 The swelling height measuring device X shown measures the swelling height of the water-absorbent resin composition. Figure 1 The swelling height measuring device X shown in the figure comprises a moving distance measuring device 1, a concave circular cup 2 (45 mm in height, 90 mm in outer diameter, 40 mm in depth of the concave portion, 80 mm in inner diameter of the concave portion), a plastic convex circular cylinder 3 (79 mm in outer diameter, 60 through holes 7 with a diameter of 2 mm evenly arranged on the contact surface with the water-absorbent resin composition), and a nonwoven fabric 4 (weight per unit area 11 g / m 2 The swelling height measuring device X can measure the displacement of the distance moved by the convex circular cylinder 3 in units of 0.01 mm using the laser 6. The concave circular cup 2 can evenly spread a predetermined amount of the water-absorbent resin composition. The convex circular cylinder 3 can evenly apply a load of 90 g to the water-absorbent resin composition 5 as a sample.

[0184] First, 0.2 g of the sample (water-absorbent resin composition 5) is uniformly spread in the concave circular cup 2, and a nonwoven fabric 4 is laid on it. Then, the convex circular cylinder 3 is gently placed on the nonwoven fabric 4, and the laser 6 of the sensor of the moving distance measuring device 1 is set to reach the center of the cylinder 3. Ion exchange water adjusted to 20° C. in advance is poured into the concave circular cup 2 through the through hole 7 of the convex circular cylinder 3 to swell the water-absorbent resin composition 5. The time when the laser senses that the water-absorbent resin composition 5 is swollen and the convex circular cylinder 3 is pushed up is regarded as the start of water absorption (0 seconds) (automatic measurement starts when a displacement of 0.5 mm occurs), and the distance (the displacement difference of the convex circular cylinder 3 in the direction perpendicular to the bottom surface of the concave part of the concave circular cup 2) by which the water-absorbent resin composition 5 is swollen and the convex circular cylinder 3 is pushed up is measured. The water level of the ion exchanged water was checked every 3 seconds from the start of the injection of the ion exchanged water, and the injection of the ion exchanged water was continued intermittently so that the water surface was maintained at a height near the flat surface of the flat plate portion of the convex circular cylindrical body 3. 30 seconds after the moment when the water-absorbent resin composition 5 started to absorb water (more precisely, the moment when the water-absorbent resin composition absorbed a very small amount of ion exchanged water and the cylindrical body 3 was pushed up by 0.5 mm), the distance by which the convex circular cylindrical body 3 was pushed up (including the height (0.5 mm) by which the cylindrical body 3 was pushed up at the moment when the water absorption started) was recorded as the 30-second swelling height.

[0185] (Measurement of gel viscosity retention rate)

[0186] The gel viscosity of the water-absorbent resin composition was measured by adjusting the temperature of the swollen gel to 25±0.5° C. using a Brookfield type rotational viscometer (Vismetron viscometer VDH2, manufactured by Shibaura Systems Co., Ltd., rotor No. 5, rotation speed 10 rpm). The gel viscosity was measured in a state where the gel was placed in a 200 mL glass beaker with an inner diameter of 64 mmφ to a height of 65 mm.

[0187] 1500 g of ion exchange water was added to a 2L beaker, and the mixture was stirred at 600 rpm using a magnetic stirring bar (cylindrical shape with a diameter of 8 mm × a length of 30 mm, without a ring). 1.5 g of the water-absorbent resin composition was added to the vortex generated by the stirring, and then stirred for 1 hour. Then, the mixture was filtered using a sieve with a mesh size of 75 μm and allowed to stand for 30 minutes. The gel viscosity of the swollen gel thus obtained was immediately measured as the "initial gel viscosity". The swollen gel after the measurement was immediately placed in a 250 mL glass heat-resistant bottle with a bottom shape of 70 mmφ and a mouth shape of 42 mmφ, and allowed to stand in a hot air dryer (manufactured by ADVANTEC, FV-320) at 50±2°C. The viscosity of the swollen gel was measured after 18 days, and the gel viscosity retention rate S was calculated by the following formula (I) from the value of the gel viscosity after 18 days.

[0188] Gel viscosity retention rate S = B / A (I)

[0189] (In formula (I), A represents the initial gel viscosity (mPa·s), and B represents the gel viscosity after 18 days (mPa·s))

[0190] (Determination of water stop rate)

[0191] use Figure 2 The measuring device shown is used to evaluate the water-stopping performance of the water-absorbent resin composition. Figure 2 The measuring device shown is formed by a cylindrical container 8 made of acrylic resin (hereinafter, recorded as cylindrical container (A)), a cylindrical container 9 made of acrylic resin (hereinafter, recorded as cylindrical container (B)) and a swollen water-absorbent resin composition 15. A nylon mesh (250 mesh) 11 having the same size as the outer diameter of the cylindrical container (A) is bonded to the bottom of the cylindrical container (A). The cylindrical container (A) has an inner diameter of 20 mm, an outer diameter of 25 mm, a height of 120 mm, and a weight of 31 g. A nylon mesh (250 mesh) 10 having the same size as the outer diameter of the cylindrical container (B) is bonded to the bottom of the cylindrical container (B). The inner diameter of the cylindrical container (B) is 26 mm, the outer diameter is 38 mm, and the height is 120 mm. The cylindrical container (A) is configured to be able to move up and down without resistance inside the cylindrical container (B). 0.20 g of the water-absorbent resin composition was uniformly added to the cylindrical container (B), and then the cylindrical container (A) was inserted into the cylindrical container (B) from the top to form a measuring portion.

[0192] A metal mesh 14 with a mesh size of 1.8 mm (50 mm×50 mm) was placed at the bottom of a petri dish 13 having an inner diameter of 90 mm and a depth of 15 mm and containing 50 g of ion exchange water 12. The nylon mesh sheet 10 side of the measurement part was placed on the metal mesh 14, thereby causing the water-absorbent resin composition 15 in the measurement part to swell for 30 minutes, and the swollen gel thus formed was recovered in a 250 mL glass heat-resistant bottle having an outer shape of 70 mmφ at the bottom and an outer shape of 42 mmφ at the mouth. The same operation as above was repeated again to form a swollen gel, which was recovered in the same glass heat-resistant bottle as in the first operation, and a swollen gel corresponding to 0.40 g of the water-absorbent resin composition before swelling was obtained. The glass heat-resistant bottle was placed in a hot air dryer (manufactured by ADVANTEC, FV-320) at 90±2°C and heated for 42 hours. The heated gel was returned to room temperature, and then the entire amount of the gel was transferred to a 500mL beaker, and ion exchange water was added to make the whole (the entire amount of the gel and the ion exchange water) 400g. A magnetic stirring bar (cylindrical with a diameter of 8mm×length of 30mm, without ring) was used to stir at 600rpm for 1 hour, and then filtered using a sieve with a mesh of 75μm to recover the filtrate. The obtained filtrate was further filtered using a Kiriyama funnel (filter paper: ADVANTEC, No.6) to recover the filtrate.

[0193] 50 g of the filtrate obtained as above was taken into a weighed 100 mL beaker which was previously kept constant at 140° C. The filtrate in the beaker was heated in a hot air dryer (manufactured by ADVANTEC, FV-320) at 140° C. for 15 hours to remove moisture, and the mass W (g) of the remaining solid content was measured. The water-stopping performance was quantified by the following formula (II) to evaluate the water-stopping rate.

[0194] Water stop rate (%) = [1-(W / 50) × 400 / 0.4] × 100 (II)

[0195]

[0196] The evaluation results of the water-absorbent resin compositions obtained in each example and comparative example are shown in Table 1. It was confirmed that the water-absorbent resin compositions obtained in each example maintained a gel state under the conditions of heating at 90°C for 42 hours, and as can be seen from Table 1, the water-stopping rate of each water-absorbent resin composition exceeded 25%. These results can be said to support that the gel state can be maintained for a long time even in the use environment of power cables or similar environments, and high water-stopping performance can be sustained.

[0197] In addition, as can be seen from Table 1, when the water-absorbent resin composition has a predetermined iron (III) chelate stability constant, the gel viscosity retention rate S is 10% or less. These results show that the water-absorbent resin composition obtained in Examples has the property of being relatively easily decomposed when released into the natural world.

[0198] As described above, the water-absorbent resin composition obtained in the examples has high water-stopping performance and is easily degradable when released into the natural world, and can be suitably used as a water-stopping material.

Claims

1. A water-absorbent resin composition comprising water-absorbent resin particles and a chelating agent, The iron (III) chelation stability constant (logKML) of the chelating agent is 19.0 or more and 24.0 or less, The water-absorbent resin composition has a 30-second swelling height of 6.0 mm or more.

2. The water-absorbent resin composition according to claim 1, wherein The chelating agent is contained in an amount of 0.001 to 3.00 parts by mass based on 100 parts by mass of the water-absorbent resin particles.

3. The water-absorbent resin composition according to claim 1 or 2, wherein The water-absorbent resin particles have a structure in which a polymer of a water-soluble ethylenically unsaturated monomer is cross-linked.

4. A waterproof material comprising the water-absorbent resin composition according to claim 1 or 2.

5. A cable comprising the waterproof material according to claim 4.

Citation Information

Patent Citations

  • Water cut-off material and water cut-off method for underground cable with protective tube

    JP2014147281A